2019
DOI: 10.3171/2018.4.jns172995
|View full text |Cite
|
Sign up to set email alerts
|

Reduced long-term cost and increased patient satisfaction with rechargeable implantable pulse generators for deep brain stimulation

Abstract: OBJECTIVEDeep brain stimulation (DBS) has revolutionized the treatment of neurological disease, but its therapeutic efficacy is limited by the lifetime of the implantable pulse generator (IPG) batteries. At the end of the battery life, IPG replacement surgery is required. New IPGs with rechargeable batteries (RC-IPGs) have recently been introduced and allow for decreased reoperation rates for IPG replacements. The authors aimed to examine the merits and limitations of these devices.METHODSThe authors reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…20 Thus, the risk-profile associated with pediatric STN-DBS in the present study seems to be comparable to that of other pediatric DBS treatment studies. Fortunately, the problems caused by battery depletion can nowadays be resolved by the use of new IPGs with rechargeable batteries, which reduces financial costs, reduces surgery-related health risks, and improves the patient's satisfaction with the DBS treatment, 23 especially in pediatric patient populations. 24 Nonetheless, a major goal of pediatric and adult DBS treatment studies in general remains to reduce the risk of adverse side effects while not affecting or even improving the clinical benefits of DBS.…”
Section: Discussionmentioning
confidence: 99%
“…20 Thus, the risk-profile associated with pediatric STN-DBS in the present study seems to be comparable to that of other pediatric DBS treatment studies. Fortunately, the problems caused by battery depletion can nowadays be resolved by the use of new IPGs with rechargeable batteries, which reduces financial costs, reduces surgery-related health risks, and improves the patient's satisfaction with the DBS treatment, 23 especially in pediatric patient populations. 24 Nonetheless, a major goal of pediatric and adult DBS treatment studies in general remains to reduce the risk of adverse side effects while not affecting or even improving the clinical benefits of DBS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported an increased incidence of infections with repeated IPG replacements [ 69 , 70 ], but one study did not find such an association [ 71 ]. Nevertheless, the use of a rechargeable IPG over a 9-year period (the initially approved lifespan of Activa RC) has been estimated to lead to savings of $60,900 based on a single-center study involving 206 patients [ 72 ]. Since rechargeable IPGs became available, many patients have been switched to rechargeable devices, and some have even received rechargeable IPGs during initial DBS implantation [ 72 , 73 ].…”
Section: Choosing the Best Systemmentioning
confidence: 99%
“…Nevertheless, the use of a rechargeable IPG over a 9-year period (the initially approved lifespan of Activa RC) has been estimated to lead to savings of $60,900 based on a single-center study involving 206 patients [ 72 ]. Since rechargeable IPGs became available, many patients have been switched to rechargeable devices, and some have even received rechargeable IPGs during initial DBS implantation [ 72 , 73 ]. Patient surveys have demonstrated that the vast majority of patients find the recharging process to be easy, and the incidence of adverse events and temporary interruptions in therapy is low [ 67 , 72 , 73 ].…”
Section: Choosing the Best Systemmentioning
confidence: 99%
“…These rlPGs have a longevity of at least 15 years in contrast to the non-rechargeable IPGs showing a mean longevity of 3-5 years. The major advantage is that patients need fewer replacement surgeries while a disadvantage is that patients must charge the rIPGs a few times a week [32].…”
Section: Advances In Dbs Technologymentioning
confidence: 99%